2008
DOI: 10.1111/j.1538-7836.2008.02911.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diagnosed chronic immune thrombocytopenic purpura in the US: analysis of a large US claim database: a rebuttal

Abstract: To cite this article: Feudjo-Tepie MA, Robinson NJ, Bennett D. Prevalence of diagnosed chronic immune thrombocytopenic purpura in the US: analysis of a large US claim database: a rebuttal. J Thromb Haemost 2008; 6: 711-2. See also Segal JB, Powe NR. Prevalence of immune thrombocytopenia: analyses of administrative data. J Thromb Haemost 2006; 4: 2377-2383; Segal JB, Powe NR. Prevalence of diagnosed chronic immune thrombocytopenic purpura in the US: analysis of a large US claim database: reply to a rebuttal. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 6 publications
2
47
1
2
Order By: Relevance
“…where prevalence of chronic ITP increased with age and was higher among females. 19 This current analysis of GPRD data indicates the same pattern;…”
Section: Statistical Analysesmentioning
confidence: 55%
See 2 more Smart Citations
“…where prevalence of chronic ITP increased with age and was higher among females. 19 This current analysis of GPRD data indicates the same pattern;…”
Section: Statistical Analysesmentioning
confidence: 55%
“…This was expected, given the female preponderance in ITP incidence. 17,28 In GPRD, the difference in prevalence between elderly female patients ≥65 years of age administrative data, [19][20][21] whereas cases within the present study were defined by electronic medical records. In addition, earlier data were from the US, whilst these were from the UK.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombocytopenia places patients at higher risk for minor and more serious bleeding, such as intracranial hemorrhage (ICH) [3]. Estimates of ITP incidence range between 2 and 5 cases per 100 000 per year in children who are younger than 15 years old [4][5][6]; prevalence estimates range between 4.1 and 12.6 cases per 100 000, depending on age, with a mean prevalence of approximately 7.2 cases per 100 000 in children younger than 18 years old [7][8]. Approximately 75% of pediatric ITP cases are newly diagnosed and persistent, with the remaining cases considered chronic [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Armed with their validated definition, the authors then set out to determine the frequency of ITP without restrictions, something that had previously only been done using databases of managed health care plans, limited to age groups or by point-prevalence questionnaires [18][19][20][21]. The authors found that the average annual prevalence of ITP was 8.1 per 100,000 children and 12.1 per 100,000 adults.…”
mentioning
confidence: 99%